Shaking B Mediates Synaptic Coupling between Auditory Sensory Neurons and the Giant Fiber of Drosophila melanogaster. - Adeline P Pézier; Sami H Jezzini; Jonathan P Bacon; Jonathan M Blagburn (PLoS ONE)
The Johnston's Organ neurons (JONs) form chemical and electrical synapses onto the giant fiber neuron (GF), as part of the neuronal circuit that mediates the GF escape response in Drosophila melanogaster. The purpose of this study was to identify which of the 8 Drosophila innexins (invertebrate gap junction proteins) mediates the electrical connection at this synapse. The GF is known to express Shaking B (ShakB), specifically the ShakB(N+16) isoform only, at its output synapses in the thorax. The shakB2 mutation disrupts these GF outputs and also abolishes JON-GF synaptic transmission. However, the identity of the innexin that forms the presynaptic hemichannels in the JONs remains unknown. We used electrophysiology, immunocytochemistry and dye injection, along with presynaptically-driven RNA interference, to investigate this question. The amplitude of the compound action potential recorded in response to sound from the base of the antenna (sound-evoked potential, or SEP) was reduced by RNAi of the innexins Ogre, Inx3, Inx6 and, to a lesser extent Inx2, suggesting that they could be required in JONs for proper development, excitability, or synchronization of action potentials. The strength of the JON-GF connection itself was reduced to background levels only by RNAi of shakB, not of the other seven innexins. ShakB knockdown prevented Neurobiotin coupling between GF and JONs and removed the plaques of ShakB protein immunoreactivity that are present at the region of contact. Specific shakB RNAi lines that are predicted to target the ShakB(L) or ShakB(N) isoforms alone did not reduce the synaptic strength, implying that it is ShakB(N+16) that is required in the presynaptic neurons. Overexpression of ShakB(N+16) in JONs caused the formation of ectopic dye coupling, whereas ShakB(N) prevented it altogether, supporting this conclusion and also suggesting that gap junction proteins may have an instructive role in synaptic target choice.